Principles of astrogliopathology: from reactivity to atrophy and degeneration - Verkhratsky, Alexei (Henry Stewart Talks, 2022)
General astrogliopathology, Astrocytes are the main homeostatic cells of the brain, Astrocytes are involved in all brain pathologies, Glial cells and reactive astrogliosis, Pathological remodelling of astrocytes, Astroglial atrophy in neurological diseases, Astrocyte atrophy and loss of capabilities in Alzheimer’s disease, Astroglial atrophy is associated with psychiatric diseases and neurodegeneration, Atrophic AD astrocytes fail to support BBB integrity, Atrophic AD astrocytes fail to mount reactive astrogliotic response, Lifestyle changes and astrocyte rescue